2009
DOI: 10.1159/000208800
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine Is an Indicator of Nutritional Status in Adolescent Girls with Eating Disorders

Abstract: Aim: Circulating thyroid hormone concentrations are influenced by nonthyroidal disease and changes in nutritional status. We studied thyroid hormones as possible indicators of nutrition in adolescent girls with eating disorders. Method: Blood samples for analyses of thyroid hormones were obtained at 360 assessments of 298 patients and biweekly during 42 treatment periods in 36 patients. Results: At assessment, when most of the girls were on a weight losing course, serum triiodothyronine (T3) concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…D6D is, however, also regulated by hormones such as insulin and thyroid hormones (26,27). These are subject to nutritional regulation and are low in ED with weight loss (28,29). The hormonal effects of starvation on D6D thus appear to override the disinhibition by low PUFA availability.…”
Section: Discussionmentioning
confidence: 99%
“…D6D is, however, also regulated by hormones such as insulin and thyroid hormones (26,27). These are subject to nutritional regulation and are low in ED with weight loss (28,29). The hormonal effects of starvation on D6D thus appear to override the disinhibition by low PUFA availability.…”
Section: Discussionmentioning
confidence: 99%
“…Goal weights typically take into account patient’s height, age, premorbid growth curve percentiles for height and weight, prior growth trajectory, growth potential, pubertal stage, anthropometric measurements and other physiological factors [1]. However, ROM does not only depend on reaching goal weight, as endocrine markers such as luteinizing hormone, estradiol, and triiodothyronine can also be useful in determining the onset or return of menses [3,18,21,22]. Notwithstanding, ROM, in conjunction with expected body weight (EBW), can serve as a yardstick to estimate goal weights for adolescent AN.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that these younger girls were more sensitive to the insults of starvation. We have previously demonstrated that circulating T3 changes rapidly with nutritional status and that this effect is considerable in premenarcheal girls (31). These girls have not yet completed puberty and longitudinal growth and this makes them vulnerable to the insults of starvation, and they have more to lose in the longer term if this weight is not recovered.…”
Section: Discussionmentioning
confidence: 99%